2016
DOI: 10.1038/ncomms13181
|View full text |Cite
|
Sign up to set email alerts
|

LWD–TCP complex activates the morning gene CCA1 in Arabidopsis

Abstract: A double-negative feedback loop formed by the morning genes CIRCADIAN CLOCK ASSOCIATED1 (CCA1)/LATE ELONGATED HYPOCOTYL (LHY) and the evening gene TIMING OF CAB EXPRESSION1 (TOC1) contributes to regulation of the circadian clock in Arabidopsis. A 24-h circadian cycle starts with the peak expression of CCA1 at dawn. Although CCA1 is targeted by multiple transcriptional repressors, including PSEUDO-RESPONSE REGULATOR9 (PRR9), PRR7, PRR5 and CCA1 HIKING EXPEDITION (CHE), activators of CCA1 remain elusive. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(124 citation statements)
references
References 47 publications
2
110
0
3
Order By: Relevance
“…The plant-specific TCP transcription factor family is known for its role in plant growth, development, immunity, and circadian clock regulation 21, 22 . Thus, we were interested in exploring the possibility of a legume MAPK targeting TCP transcription factors and adding another layer of regulation in TCP complexes.…”
Section: Resultsmentioning
confidence: 99%
“…The plant-specific TCP transcription factor family is known for its role in plant growth, development, immunity, and circadian clock regulation 21, 22 . Thus, we were interested in exploring the possibility of a legume MAPK targeting TCP transcription factors and adding another layer of regulation in TCP complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Not only TCP21, other TCPs have also been found to bind to CCA1 in yeast based studies and co-immunoprecipitation experiments (Giraud et al, 2010; Pruneda-Paz et al, 2014). A recent study also showed that TCP20 and TCP22 act as activators of CCA1 in the morning, fulfilling an important role in the circuity of the circadian clock (Wu et al, 2016). This means that TCP proteins bind to the promoters of clock genes, regulate their expression, dimerize with clock proteins and bind to downstream targets of the clock (Pruneda-Paz et al, 2009, 2014; Giraud et al, 2010; Wu et al, 2016) ( Figure 3 ).…”
Section: Tcp Functions Effect On the Cell Cycle – Direct Or Indirect?mentioning
confidence: 99%
“…A recent study also showed that TCP20 and TCP22 act as activators of CCA1 in the morning, fulfilling an important role in the circuity of the circadian clock (Wu et al, 2016). This means that TCP proteins bind to the promoters of clock genes, regulate their expression, dimerize with clock proteins and bind to downstream targets of the clock (Pruneda-Paz et al, 2009, 2014; Giraud et al, 2010; Wu et al, 2016) ( Figure 3 ). Altogether, it becomes clear that TCPs not only affect growth via the cell cycle.…”
Section: Tcp Functions Effect On the Cell Cycle – Direct Or Indirect?mentioning
confidence: 99%
“…For example, a WD repeat-containing protein, LIGHT-REGULATED WD1 (LWD1) acts as a coactivator of TCP20 and 22 in regulating expression of morning gene CIRCADIAN CLOCK ASSOCIATED1 ( CCA1 ) in Arabidopsis (Wu et al, 2016). Although TCP20 and 22 can bind to regulatory element in CCA1 promoter, even in the absence of LWDs, overexpression of TCP20 / 22 in lwd1lwd2 double mutant fails to activate CCA1 expression (Wu et al, 2016). Whether concomitant binding of TCPs and LWDs leads to any shifts in conformational state of TCPs is yet to be determined.…”
Section: Binding Site and Mechanism Of Actionmentioning
confidence: 99%